(untitled) (Revista "Boletín el Conuco", 2022)
The purpose of this article is to analyze in an explanatory way, the possible structural changes due to the economic impact of imports in the production of paddy rice in the department of Meta, which could be due to the free trade agreement with the United STATES, which was signed in 2006 and entered into force in 2012. An econometric model is implemented to determine the factors that affect the level of paddy rice production in the department of Meta for the period analyzed, which corresponds from 1991 to 2019, which is why it is considered important and relevant to analyze the influence of the area planted (in hectares), yields, imports and production (in tons); likewise, the Chow test was used to determine the structural changes in the three moments studied in the timelines used. The results showed that imports do not generate a structural change in the quantities of paddy rice production, on the contrary, as the years go by the negative impact of imports is reduced, it is concluded that imports did not represent a negative impact for the production of paddy rice in the department of Meta in the period studied, at the same time there was a growth in the areas dedicated to this crop.